An increase in p62/NBR1 levels in melioidosis patients of Sri Lanka exhibit a characteristic of potential host biomarker - Saikh, Kamal U. (J Med Microbiol, 2020)
INTRODUCTION: Melioidosis, caused by Burkholderia pseudomallei , in endemic areas, poses a challenge for treating the diseased populations without accurate diagnosis, and the disease-specific biomarkers linked with the infection have yet to be reported. Due to the invasive nature of the causative agent, Burkholderia pseudomallei , host innate effector mechanisms, including autophagy are known to be activated, resulting in differential expression of cellular proteins and immune markers. Identification of a disease-specific biomarker associated with B. pseudomallei infection will be helpful to facilitate rapid confirmation of melioidosis, which would enable early treatment and therapeutic success. AIM: We aimed to assess the levels of a host autophagy component, p62/NBR1, which function as a cargo-receptor in the process of autophagy activation leading to the degradation of ubiquitin-coated intracellular bacteria in which p62/NBR1 itself is degraded in the clearance of the pathogen. We further probed the extent of intracellular p62/NBR1 degradation and assessed its potential as a melioidosis biomarker. METHODOLOGY: We analysed peripheral blood mononuclear cell (PBMC) lysates using an ELISA-based assay for detecting cytosolic autophagy-related proteins p62/NBR1. We measured p62/NBR1 levels in diseased (confirmed B. pseudomallei infection) and non -diseased populations and utilized receiver operating characteristic (ROC) curve and max Youden index analysis for evaluating potential disease biomarker characteristics. RESULTS: Our results revealed a three to fivefold increase in p62/NBR1 levels confirmed melioidosis cases compared to uninfected healthy donors. Comparable to p62/NBR1, levels of cytosolic LC3-I levels also increased, whereas the levels of degraded membrane bound form LC3-II was low, suggesting autophagy deficiency. Proinflammatory serum cytokine response, particularly IL-6, was consistently higher alongside B. pseudomallei infection in comparison to healthy controls. CONCLUSIONS: ROC curve and max Youden index analysis suggest that increased p62/NBR1 levels in diseased populations display characteristics of a potential disease biomarker in melioidosis and illustrates that an elevated p62/NBR1 level, in conjunction with B. pseudomallei infection associated with autophagy deficiency.